(untitled) (Scientia Agricola, 2015)
Zucchini yellow mosaic virus (ZYMV) causes substantial economic losses in cucurbit crops. Although ZYMV has been present in Brazil for more than 20 years, there is little information about the biological and molecular characteristics of the isolates found in the country. This study aimed to characterize the experimental hosts, pathotypes and genetic diversity of a collection of eleven Brazilian ZYMV isolates within the coat protein gene. For biological analysis, plant species from Amaranthaceae, Chenopodiaceae, Cucurbitaceae, Fabaceae, Solanaceae, and Pedaliaceae were mechanically inoculated and pathotypes were identified based on the reaction of a resistant Cucumis melo, accession PI414723. All of the cucurbit species/varieties and Sesamum indicum were systemically infected with all isolates. The nucleotide sequence variability of the coat protein gene ranged from 82 % to 99 % compared to the corresponding sequences of ZYMV isolates from different geographical locations. No recombination event was detected in the coat protein gene of the isolates.